Un llamado a la medición del intervalo QT y su corrección en la isquemia miocárdica aguda - Chávez González, Elibet; Rodríguez González, Fernando; Cruz Elizundia, Juan M. (CorSalud, 2013)
Un llamado a la medición del intervalo QT y su corrección en la isquemia miocárdica aguda